PRODUCTION OF GLASS-CERAMICS FROM WASTE MATERIALS AND OPTIMIZATION OF THE MAIN PROCESS PARAMETERS - Biljana Angjusheva; Emilija Fidancevski; Kiril Lisichkov; Vojo Jovanov (Journal of Engineering & Processing Management, 2016)
In this study the 3D surface model was successfully applied in investigating the influence of theprocess parameters on the physical and mechanical properties of the glass-ceramics. Glassceramicswas produced from coal fly ash and waste glass through the sintering method. The rawmaterial was taken from "REK Bitola", a thermal power plant in the Republic of Macedonia.Glass-ceramics was obtained through the process of consolidation. Compacts with different ratio offly ash and waste glass were pressed at 45 MPa, sintered in the temperature interval from 1000 to1100 ℃, and isothermal time at the final temperature from 1h to 5h. The process of optimizationwas conducted on the process parameters such as quantity of glass, sintering temperature andisothermal time. According to the results of the process of optimization presented by the softwarepackage, a final model equations of the density and bending strength dependence were obtained.
Keywords: optimization; consolidation; process parameters; fly ash; glass-ceramics